The Politics of the Malayan Communist Party from 1930 to 1948 - Lockwood, David, 1953- (NUS Press, 2024)
A new evaluation of the history of the Malayan Communist Party. By 1946, the Malayan Communist Party (MCP) had become one of the most successful communist parties in Asia. From its foundation in 1930, it had built up a membership in the thousands, mainly among Chinese and Indian workers in Malaya. When the Japanese arrived, the MCP organized the Malayan People's Anti-Japanese Army (MPAJA), the only effective resistance force. After the War, when the British returned, the Party launched a legal campaign for independence, but by 1948, the MCP had surrendered its achievements and taken many members underground to launch a disastrous, failed insurrection against the British. To understand these momentous turns of history, a fresh view is required of the Malayan Communist Party as a political actor. The Politics of the Malayan Communist Party from 1930 to 1948 gives a political history of the Party and explains why the MCP self-destructed in 1948. In particular, David Lockwood questions assumptions that post-war politics led inevitably to armed struggle and questions the accepted narrative of Party Chairman Lai Tek's treachery. This is a revisionist history of a period, and political force, that has left a lasting mark on the politics of Malaya and Singapore.